Development of chrysanthemum-flavored nata de coco in syrup - Ong, Melanie; Galvez, Flor Crisanta F. (2000.)
ABSTRACT The aim of this study was to produce chrysanthemum tea flavored nata de coco by means of diffusion and equilibrium of the flavoring concentrates in the syrup where the nata was soaked. Nine set-ups were made namely 3%, 6%, and 12% concentrations with each concentration having variations of 3, 5 and 7 days soaking time. Consumer acceptability tests and statistical analyses were made to compare data obtained from the various set-ups. It was found that the set-up with least amount of chrysanthemum and shortest soaking time was not significantly different from the other set-ups in terms of consumer acceptability and the most acceptable among the treatments.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Nata de coco